2007
DOI: 10.1504/ijeb.2007.015450
|View full text |Cite
|
Sign up to set email alerts
|

National culture and its effects on knowledge communication in online virtual communities

Abstract: Online virtual communities provide a powerful means of knowledge sharing. Despite the prevalence of online virtual communities, there is a paucity of research to investigate the effect of national culture differences on knowledge sharing in online virtual communities. Are there differences between online virtual communities from different national cultures? This research studies the differences in knowledge-sharing activities between US-based and China-based online virtual communities. Hofstede's dimensions of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Even though a multitude of studies address the differences in culture [e.g., Triandis, 1995;Fukuyama, 1996;Schwartz, 1994], this study relies on Hofstede's [2001] framework to examine the cultural differences. Widely recognized among scholars and industry leaders [e.g., Siau, Nah and Ling, 2007;Li, Hess, McNab and Yu, 2009], Hofstede's framework incorporates power distance, individualism, masculinity, and uncertainty avoidance. Comparison of scores across these dimensions allows us to make systematic conclusions about the nature of the intercultural differences between Germany, Russia, and Morocco (Table 1).…”
Section: Cultural Differencesmentioning
confidence: 99%
“…Even though a multitude of studies address the differences in culture [e.g., Triandis, 1995;Fukuyama, 1996;Schwartz, 1994], this study relies on Hofstede's [2001] framework to examine the cultural differences. Widely recognized among scholars and industry leaders [e.g., Siau, Nah and Ling, 2007;Li, Hess, McNab and Yu, 2009], Hofstede's framework incorporates power distance, individualism, masculinity, and uncertainty avoidance. Comparison of scores across these dimensions allows us to make systematic conclusions about the nature of the intercultural differences between Germany, Russia, and Morocco (Table 1).…”
Section: Cultural Differencesmentioning
confidence: 99%
“…Chow et al (2000) for example show that Chinese nationals in comparison to Americans are more unwilling to transfer knowledge to an out-group member. A few others deal with cultural effects on knowledge transfer in virtual online communities (Ardichvili et al, 2006;Siau et al, 2007). Ardichvili et al (2006) found that Chinese nationals are more or less to shy to participate in such online communities.…”
Section: Introductionmentioning
confidence: 99%
“…Michailova and Hutchings (2006) reveal that distinctions between in-groups and out-groups are of critical relevance to decisions on sharing knowledge in Russia and China. Siau et al (2007) investigate the effects of national culture on knowledge sharing in online virtual communities. To facilitate an integrated adoption of KM methods and approaches in Chinese organizations, it is therefore necessarily to identify existing KM methods and their characteristics through a comprehensive document analysis of existing KM research in this regard.…”
Section: Km In Chinese Organizationsmentioning
confidence: 99%